Basic Principle of Plants Bioactive Compounds Extraction Using Various Extraction Methods - Ananda Regita Olivira; Hadi Munarko; Jariyah (Future Science, 2023)
Bioactive compounds are also defined as secondary metabolites that are present in plants. Bioactive compounds are present in a wide variety of plant materials and can be classified into several types, such as terpenoids, alkaloids, nitrogen-containing compounds, organosulfur compounds, and phenolics. Bioactive chemicals of natural origin are often found in small amounts. This occurrence has resulted in the development of more complex extraction methods. Therefore, it is crucial to carefully choose a suitable extraction technique to effectively obtain the desired bioactive components. The objective of this article is to present a comprehensive review of the several extraction techniques used to obtain bioactive compounds from plants. The extraction methods include several kinds of procedures, including both conventional and modern approaches.